Public administrators and policy analysis: beyond political science - Swain John W.
This article proposes using an analytical approach to teaching policy analysis in public administration programs. It is organized using questions raised by journalist: who, what, why where, when, and how. Although most attention is devoted to the content of such an approach, the initial portion of the article provides a rationale for taking that approach. The initial portion of the article concludes with a rejoinder to those who might be tempted to dismiss the argument out of hand because the proposed view of policy analysis is not a political science one. It is desirable to go beyond a political science view of policy analysis in teaching public policy in public administration programs to a broader concept
Keywords: Public Policy; Public Administration